Genomic Insights of Multidrug-Resistant Escherichia coli From Wastewater Sources and Their Association With Clinical Pathogens in South Africa - Mbanga, Joshua; Amoako, Daniel G.; Abia, Akebe L. K.; Allam, Mushal; Ismail, Arshad; Essack, Sabiha Y. (Frontiers in Veterinary Science, 2021)
There is limited information on the comparative genomic diversity of antibiotic-resistant Escherichia coli from wastewater. We characterized various E. coli pathotypes obtained from a wastewater treatment plant (WWTP) and its receiving waters using whole-genome sequencing to elucidate their resistomes, virulomes, mobilomes, clonality, and phylogenies. Twelve multi-drug resistant diarrheagenic E. coli isolates obtained from the WWTP and receiving river upstream and downstream of the WWTP were sequenced on an Illumina MiSeq machine. MLST analysis revealed multiple sequence types (STs), the most common being ST69 (n = 4) and ST10 (n = 2) followed by singletons belonging to ST372, ST101, ST569, ST218, ST200 and a novel sequence type ST 11351. A total of 66.7% isolates harbored β-lactamase genes with 58.3% harboring the blaTEM-1B gene and one isolate the blaCTX-M-14 and blaCTX-M-55 genes. One isolate was positive for the mcr-9 mobilised colistin resistance gene. Most antibiotic resistance genes were associated with mobile genetic support; class 1 integrons (In22, In54, In191, In369), insertion sequences (IS) and/or transposons (Tn402 or Tn21). A total of 31 virulence genes were identified across the study isolates including those for adhesion (lpfA, iha, aggR), immunity (air, gad, iss), and toxins (senB, vat, astA, sat). The virulence genes were mostly associated with IS (IS1, IS3, IS91, IS66, IS630, IS481) or prophages, which are central in their rearrangement and transfer. Heavy metal and biocide co-resistance was evident in the isolates. Comparative phylogenomic analysis with South African animal, bird, and human E. coli isolates showed frequent clustering with clinical strains. Compared to previous studies, the current study provides in-depth information regarding the genetic make-up of multi-drug resistant pathogenic E. coli in surface water used by communities in South Africa. This is a major public health concern that needs careful mitigation measures to ensure human health in the vicinity of such water bodies.